Clinical and epidemiological aspects related to the detection of adenovirus or respiratory syncytial virus in infants hospitalized for acute lower respiratory tract infection - Eduardo A. Ferone; Eitan N. Berezin; Giuliana S. Durigon; Cristiane Finelli; Maria C.C. Felicio; Juliana G. Storni; Edison L. Durigon; Danielle B. L. de Oliveira (Elsevier, 2014)
OBJECTIVE: To characterize and compare clinical, epidemiological, and laboratory aspects ofinfants with acute lower respiratory infection (ALRI) associated with the detection of adenovirus(ADV) or respiratory syncytial virus (RSV). METHODS: A preliminary respiratory infection surveillance study collected samples of nasopharyngeal aspirate (NPA) for viral research, linked to the completion of a standard protocol, from children younger than two years admitted to a university hospital with ALRI, between March of 2008 and August of 2011. Polymerase chain reaction (PCR) was used for eight viruses: ADV, RSV, metapneumovirus, Parainfluenza 1, 2, and 3, and Influenza A and B. Cases with NPA collectedduring the first 24 hours of admission, negative results of blood culture, and exclusive detection of ADV (Gadv group) or RSV (Grsv group) were selected for comparisons. RESULTS: The preliminary study included collection of 1,121 samples of NPA, 813 collected in thefirst 24 hours of admission, of which 50.3% were positive for at least one virus; RSV was identifiedin 27.3% of cases surveyed, and ADV was identified in 15.8%. Among the aspects analyzed inthe Gadv (n = 58) and Grsv (n = 134) groups, the following are noteworthy: the higher meanage, more frequent prescription of antibiotics, and the highest median of total white blood cellcount and C-reactive protein values in Gadv. CONCLUSIONS: PCR can detect persistent/latent forms of ADV, an aspect to be considered wheninterpreting results. Additional studies with quantitative diagnostic techniques could elucidatethe importance of the high frequency observed.